Calidad De Agua Usando Macroinvertebrados Como Bioindicadores Y Algunos Parámetros Fisico-Químicos En El Río Motil – La Libertad. - Del Águila Castañeda, Yolvi Augusto (2023)
The objective of this research was to determine the water quality using macroinvertebrates as bioindicators and physical-chemical parameters in the Motil - La Libertad river, by applying the Biological Monitoring Working Party (BMWP) biological index adapted for northern Peru. The procedure was based on the Protocol for sampling, analysis and evaluation of macroinvertebrate benthic fauna in fordable rivers, of the Basque Water Agency of the Basque Country. To carry out the study, 4 sampling points were selected both in spring 2021 and autumn 2022. A total of 1286 specimens were determined, distributed in 21 families and 12 orders, the largest family was Baetidae both in spring and autumn (111 and 549 specimens), for spring the sampling points P-0, P-2 and P-3 obtained poor biological quality "highly polluted waters" and P-1 regular biological quality "contaminated waters"; and for autumn the P-0 sampling point had poor biological quality "highly polluted waters" and the points P-1, P-2 and P-3 acceptable biological quality "water with signs of stress". As soon as the physical-chemical parameters were measured, pH, conductivity, dissolved oxygen, salinity, total dissolved solids, temperature, total phosphorus, sulfate, nitrate and copper, which complied with the Environmental Quality Standards (ECA) with the exception of pH. of P-0 for category 4 "Conservation of the aquatic environment" according to established supreme decree No. 004 - 2017 MINAM